STUDY OF GERMAN, UZBEK, KARAKALPAK PROVERBS IN LINGUISTIC AND METHODOLOGICAL ASPECTS - Toreniyazova, Aysuliw Yeliubaevna (Innovative Development in Educational Activities, 2024)
This scientific article investigates the linguistic and methodological aspects of German, Uzbek, and Karakalpak proverbs. Proverbs are an essential part of a language’s cultural heritage, reflecting the collective wisdom and values of a community. By studying proverbs from different languages, we can gain insights into linguistic patterns, cultural nuances, and methodological approaches employed in their analysis. This research explores the structural and semantic characteristics of German, Uzbek, and Karakalpak proverbs and provides a comparative analysis of their respective idiomatic expressions. The methodology employed includes corpus-based analysis, semantic categorization, and cultural interpretation. The findings contribute to our understanding of the linguistic and cultural diversity inherent in proverbs and emphasize the importance of preserving and studying these linguistic gems.